A review of neococcid scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) based on the morphology of the adult males - Hodgson, Chris (Zootaxa, 2020)
The importance of adult male morphology in elucidating the phylogeny of scale insects (Coccomorpha) was first suggested by Balachowsky and Ferris in the late 1930s. However, the first extensive comparisons of adult male morphology were made by Jancke (1955) and Theron (1958), both of whom looked at the morphology of various groups of Coccomorpha. Theron’s study, under the guidance of K.L. Boratyński, set a new standard for detail and accuracy (although he did not describe the setae). These studies were closely followed by Beardsley (1962), who described the adult males of 30 mealybug species from Hawaii, and then by three more of Boratyński’s students who produced highly significant monographs on particular families, namely Ghauri (1962) who described 26 species of Diaspididae, Giliomee (1967a) who described 22 species of Coccidae and Afifi (1968) who described 17 species of Pseudococcidae and 7 species of Eriococcidae. Since then, the adult males of more than 300 neococcoid species have been described in considerable detail (Appendix A). Adult males of a further 48 species are described or redescribed and illustrated in this monograph (Acanthococcus adenostomae (Ehrhorn), Eriochiton armatus Brittin; Apiomorpha munita tereticornuta Gullan; A. ovicola (Froggatt); A. pharetrata (Schrader); A. rosaeformis (Froggatt); A. spinifer Froggatt; Dactylopius coccus (Costa); Callococcus leptospermi (Maskell);  Lachnodius ?eucalypti (Maskell); Tanyscelis verrucula (Froggatt); Beesonia dipterocarpi Green; Parastictococcus brachystegiae (Hall); P. hargreavesi (Vayssière); P. multispinosus (Newstead); Stictococcus intermedius Newstead; S. vayssierei Richard; Conchaspis angraeci Cockerell; C. capensis Linnaeus; C. socialis Green; C. vayssierei Mamet; Leucaspis gigas (Maskell); Labidaspis myersi (Green); Allokermes galliformis (Riley); Kermes shastensis Ehrhorn; Kermes sp.; Tachardina aurantiaca (Cockerell); Tachardiella sp.; Cerococcus artemisiae (Cockerell); Antecerococcus indicus (Maskell); A. ornatus (Green); Bambusaspis delicata (Green); B. longa (Green); Asterolecanium petrophilae (Fuller); Hsuia cheni Borchsenius; Aclerda arundinariae McConnell; A. distorta Green; A. tillandsiae Howell; A. tokionis Cockerell; Aclerda sp. A; Aclerda sp. B; Luzulaspis caricis (Ehrhorn); Akermes scrobiculatus (Maskell); A. pingue (Maskell); Cardiococcus major (Maskell); Ctenochiton serratus Green; C. eucalypti Maskell, and ?Pulvinaria dodonaeae Maskell). This paper summarises the data from all of these descriptions, and provides diagnoses for the adult male morphology for all of the neococcoid families and other taxa discussed here. Because our concept of the “Eriococcidae” remains uncertain, extra attention has been payed to the taxa considered to be most closely involved. At least 1 illustration is included of an adult male of each of the taxa (mainly families) discussed here. Identification keys are provided for most of the males described to-date.